Open Education International Perspectives in Higher Education - Bliss, TJ; Blessinger, Patrick (Open Book Publishers, 2016)
"This insightful collection of essays explores the ways in which open education can democratise access to education for all. It is a rich resource that offers both research and case studies to relate the application of open technologies and approaches in education settings around the world. Global in perspective, this book argues strongly for the value of open education in both the developed and developing worlds. Through a mixture of theoretical and practical approaches, it demonstrates that open education promotes ideals of inclusion, diversity, and social justice to achieve the vision of education as a fundamental human right. A must-read for practitioners, policy-makers, scholars and students in the field of education."